2004
DOI: 10.1023/b:jmsm.0000010099.58361.1b
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity of E-glass fiber weave preimpregnated with novel biopolymer

Abstract: The aim of this study was to investigate cytotoxicity of composition of E-glass fibers and novel biopolymer of poly(hydroxyproline). Growth and proliferation of the human gingival fibroblast cells on the surface of the materials was evaluated. The number of cells grown and proliferated on cell culture plastic was used as a control. Bi-directional fiber weaves were preimpregnated with poly(hydroxyproline). Cytotoxicities of the preimpregnated and nonimpregnated materials were evaluated bythe release of lactate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…E-glass fibers having silane containing surface sizing without resin matrix have shown no signs of cytotoxity in fibroblast or osteoblast cell culture studies [37][38][39]. In another study, rat bone-marrow derived osteoblast-like cells were harvested and cultured on experimental FRC plates and on commercially pure titanium plates as control [40].…”
Section: Biological Considerationsmentioning
confidence: 99%
“…E-glass fibers having silane containing surface sizing without resin matrix have shown no signs of cytotoxity in fibroblast or osteoblast cell culture studies [37][38][39]. In another study, rat bone-marrow derived osteoblast-like cells were harvested and cultured on experimental FRC plates and on commercially pure titanium plates as control [40].…”
Section: Biological Considerationsmentioning
confidence: 99%
“…The degradable component was based on corn starch and cellulose acetate blends [18]. In the present study, the aim is to synthesize an experimental polyamide based on an amino acid of trans-4-hydroxy-L-proline that has been used as a hydrophilic pore generating material in nondegradable acrylic bone cement [19,20]. By adding the hydrophilic porogen oligomer with low molecular weight to nondegradable matrixes, it is possible to create porosity during the first week in moist conditions [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Cell culture study by fibroblasts with silanized E-glass fibers without the resin matrix has shown no signs of cytotoxicity, as it has been also demonstrated with fibroblasts by agar diffusion cytotoxicity test and animal experiments [30,[56][57][58][59][60][61][62]. In the form of FRC implant, glass fibers are covered by the thermoset polymer matrix and the only areas where the glass fibers are exposed are located at the margins of the implant which have been finished mechanically or by laser ablation.…”
Section: Biocompatibility Of Frc Materialsmentioning
confidence: 99%